Simulasi CFD Performa Aerodinamika Rotor Turbin Angin Counter-Rotating melalui Variasi Rasio Kecepatan Tip Blade dengan Solidity Konstan - Verdy A. Koehuan; Jani F. Mandala (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2020)
The aim of this research is to numerically study the aerodynamic parameters of the rotor, namely the tip speed ratio, stall phenomenon, and flow losses due to the vortex along the turbine rotor blade. Numerical analysis through the CFD or computational fluid dynamics simulation method is applied to counter-rotating wind turbines to predict and analyze the aerodynamic performance of the rotor through variations in the diameter ratio, distance ratio to tip speed ratio on constant rotor solidity. The performance of this turbine rotor is represented as the output power and the power coefficient of each research variable to obtain the best performance as well as the turbine rotor design as the research output. CFD prediction results show a trend that is closer to the experiment, where the maximum power coefficient value occurs at TSR = 6 with CP, max = 0.453 which is 3.09% lower than the experimental results. This shows that the CFD simulation model is validated in almost all of the varied TSR ranges, except at high TSR it tends to move away from the experiment. Flow fluctuation after passing through the second rotor is caused by the vortices in the hub and blade tips of the front and rear rotors. Rotors with misaligned blade tips (D1/D2 <1.0 and D1/D2 > 1.0) are more volatile than rotors with aligned tip blade (D1/D2 = 1.0).